Ketamine Use in Prehospital and Hospital Treatment of the Acute Trauma Patient: A Joint Position Statement. (4th July 2021) - Morgan, Margaret M.; Perina, Debra G.; Acquisto, Nicole M.; Fallat, Mary E.; Gallagher, John M.; Brown, Kathleen M.; Ho, Jeffrey; Burnett, Aaron; Lairet, Julio; Rowe, Dennis; Gestring, Mark L.
Abstract: The American College of Surgeons Committee on Trauma (ACS-COT), the American College of Emergency Physicians (ACEP), the National Association of State EMS Officials (NASEMSO), the National Association of EMS Physicians (NAEMSP) and the National Association of EMTs (NAEMT) have previously offered varied guidance on the use of ketamine in trauma patients. The following consensus statement represents the collective positions of the ACS-COT, ACEP, NASEMSO, NAEMSP and NAEMT. This updated uniform guidance is intended for use by emergency medical services (EMS) personnel, EMS medical directors, emergency physicians, trauma surgeons, nurses and pharmacists in their treatment of the trauma patient in both the prehospital and hospital setting.